Sphingosine-1-Phosphate and Its Signal Modulators Alleviate Psoriasis-Like Dermatitis: Preclinical and Clinical Evidence and Possible Mechanisms - Liu, Liu; Wang, Jiao; Li, Hong-jin; Zhang, Shuo; Jin, Meng-zhu; Chen, Si-ting; Sun, Xiao-ying; Zhou, Ya-qiong; Lu, Yi; Yang, Dan; Luo, Ying; Ru, Yi; et al. (Frontiers in Immunology, 2021)
Background: Psoriasis is an autoimmune skin disease associated with lipid metabolism. Sphingosine-1-phosphate (S1P) is a bioactive lipid that plays a key role in the development of autoimmune diseases. However, there is currently a lack of comprehensive evidence of the effectiveness of S1P on psoriasis. Objective: To assess the efficacy and possible mechanism of S1P and its signal modulators in the treatment of psoriasis-like dermatitis. Methods: Six databases were searched through May 8, 2021, for studies reporting S1P and its signal modulators. Two reviewers independently extracted information from the enrolled studies. Methodological quality was assessed using SYRCLE’s risk of bias tool. RevMan 5.3 software was used to analyze the data. For clinical studies, the Psoriasis Area and Severity Index score were the main outcomes. For preclinical studies, we clarified the role of S1P and its regulators in psoriasis in terms of phenotype and mechanism. Results: One randomized double-blind placebo-controlled trial and nine animal studies were included in this study. The pooled results showed that compared with control treatment, S1P receptor agonists (mean difference [MD]: −6.80; 95% confidence interval [CI]: −8.23 to −5.38; p<0.00001), and sphingosine kinase 2 inhibitors (MD: −0.95; 95% CI: −1.26 to −0.65; p<0.00001) alleviated psoriasis-like dermatitis in mice. The mechanism of S1P receptor agonists in treating psoriasis might be related to a decrease in the number of white blood cells, topical lymph node weight, interleukin-23 mRNA levels, and percentage of CD3+ T cells (p<0.05). Sphingosine kinase 2 inhibitors ameliorated psoriasis in mice, possibly by reducing spleen weight and cell numbers (p<0.05). Conclusions: S1P receptor agonists and sphingosine kinase 2 inhibitors could be potential methods for treating psoriasis by decreasing immune responses and inflammatory factors.